Utilising disturbance metrics in traffic safety estimation. Issue 6 (9th April 2021) - Azizi, Leila; Hadi, Mohammed
Abstract : There have been limited efforts to investigate the potential of using detailed trajectory data obtained from connected vehicles and/or other sensors in deriving metrics for use in real-time assessment of traffic safety. This study investigated the use of disturbance metrics for this purpose. The disturbance metrics considered were the number of oscillations (NoO) and a measure of disturbance durations in terms of the time exposed time-to-collision index (TETIndex). The time exposed time-to-collision (TET) has been widely used as a safety surrogate measure, but there is no study on the identification of its thresholds to justify activating plans to mitigate unsafe conditions in real-time operations. This study found a TETIndex of 0.03 and NoO of 10% can be used to recognise unsafe conditions in the case study of this research. Since estimation of the TETIndex requires the location and speed of both leading and following vehicles and therefore cannot be measured accurately with low sample sizes of vehicle trajectories, a regression model was derived to estimate the TETIndex based on speed parameters. It was also found that the investigated disturbance metrics and associated models and thresholds are significantly related to crash occurrence and can thus be used in the activation of transportation management strategies to reduce the probability of unsafe traffic and ease traffic disturbances that have an adverse impact on traffic safety.